The golem at large : - Collins, Harry M. (Cambridge University Press, 1998)
In the very successful and widely discussed first volume in the Golem series, The Golem: What You Should Know About Science, Harry Collins and Trevor Pinch likened science to the Golem, a creature from Jewish mythology, a powerful creature which, while not evil, can be dangerous because it is clumsy. In this second volume, the authors now consider the Golem of technology. In a series of case studies they demonstrate that the imperfections in technology are related to the uncertainties in science described in the first volume. The case studies cover the role of the Patriot anti-missile missile in the Gulf War, the Challenger space shuttle explosion, tests of nuclear fuel flasks and of anti-misting kerosene as a fuel for airplanes, economic modeling, the question of the origins of oil, analysis of the Chernobyl nuclear disaster, and the contribution of lay expertise to the analysis of treatments for AIDS.